A propos de la racine lhm dans Proverbes 18:8 - Masson, Michel (Vetus Testamentum, 2021)
This note proposes to interpret the global meaning of the root להם as “to devour” and, as a consequence, to understand Prov 18:8 as “the plotter’s words gnaw at his victim’s guts.”